Elective distribution of resistance to beta-lactams among Enterobacter cloacae genetic clusters. Issue 3 (September 2018) - Garinet, Simon; Fihman, Vincent; Jacquier, Hervé; Corvec, Stéphane; Le Monnier, Alban; Guillard, Thomas; Cattoir, Vincent; Zahar, Jean-Ralph; Woerther, Paul-Louis; Carbonnelle, Etienne; Wargnier, Alain; Kernéis, Solen; et al.
Highlights: " Enterobacter cloacae " clinical isolates belong to different genetic clusters. ESBL expression is selectively distributed among genetic clusters. Rapid identification of genetic clusters would improve the targeting of empirical therapy. Summary: Objectives: The Enterobacter cloacae complex (Ecc), routinely referred to as " E. cloacae " in clinical microbiology, encompasses several species with 12 genetic clusters and one sequence crowd that can be identified based on hsp60 sequencing. Little is known about the pathogenicity and distribution of resistance to antibiotics among the Ecc. Methods and Results: In this prospective multicentre study, a total of 193 Ecc clinical isolates were collected from 10 academic hospitals distributed nationally across France and identified at the genetic cluster level on the basis of hsp60 sequencing. E. hormaechei isolates, which belong to clusters VI-VIII, were the largest group (53%), followed by cluster III that accounted for 28% of clinical isolates. All other Ecc clusters were present except cluster VII ( E. hormaechei subsp. hormaechei ). Cephalosporinase overproduction and ESBL were significantly more present in E. hormaechei (33% and 20%) than in other clusters (19% and 3%, respectively). Conclusions: These results suggest that rapid identification of " E. cloacae " at the genetic cluster level could improve adequacy of empirical antibiotic treatment and reduce the unnecessary use of broad spectrum antibiotics.